Response of the REWARD detection system to the presence of a Radiological Dispersal Device. (May 2016) - Luís, R.; Fleta, C.; Balbuena, J.; Baptista, M.; Barros, S.; Disch, C.; Jumilla, C.; Lozano, M.; Marques, J.G.; Vaz, P.
Abstract: The objective of the REWARD project consisted in building a mobile system for real time, wide area radiation surveillance, using a CdZnTe detector for gamma radiation and a neutron detector based on novel silicon technologies. The sensing unit includes a GPS system and a wireless communication interface to send the data remotely to a monitoring base station, where it will be analyzed in real time and correlated with historical data from the tag location, in order to generate an alarm when an abnormal situation is detected. The main objective of this work consisted in making predictions regarding the behavior of the REWARD system in the presence of a Radiological Dispersion Device (RDD), one of the reference scenarios foreseen for REWARD, using experimental data and the Monte Carlo simulation program MCNP6. Experimental tests were performed at the Fire Brigades Facilities in Rome and at the Naples Fire Brigades. The response of the REWARD detection system to the presence of an RDD is predicted and discussed. Highlights: A prototype mobile system for real-time, wide-area radiation surveillance was built. Experimental measurements and Monte Carlo simulations were used to test the system. The system is suitable to detect and identify radiation sources in threat scenarios.